Associations of Fentanyl, Sufentanil, and Remifentanil With Length of Stay and Mortality Among Mechanically Ventilated Patients: A Registry-Based Cohort Study - Wang, Wen; He, Qiao; Wang, Mingqi; Kang, Yan; Ji, Peng; Zhu, Shichao; Zhang, Rui; Zou, Kang; Sun, Xin (Frontiers in Pharmacology, 2022)
Background: As the first-line treatment for mechanically ventilated patients with critical illness, fentanyl and its analogues (e.g. sufentanil and remifentanil) are commonly used in intensive care unit (ICU). However, the pharmacokinetics, metabolism and potency of these agents differed. Their effects on clinical outcomes has not been well understood. Materials and Methods: Using a well-established registry, we conducted a cohort study. Patients who consistently underwent mechanically ventilation (MV) for more than 24 hours were identified. We used a time-varying exposure definition, in which we coded each type of opioids as prescribed or not prescribed on each day from initiation of MV to extubation and ICU discharge. We used Fine-Gray competing risk models to compare the effects of fentanyl, sufentanil, and remifentanil on hazards for extubation, ventilator mortality, ICU discharge, and ICU mortality. All models were adjusted using a combination of fixed-time and time-varying covariates. Missing data were imputed using multiple imputation by chained equations. Results: A total of 8165 patients were included. There were respectively 4778, 4008 and 2233 patients receiving at least one day of fentanyl, sufentanil and remifentanil. Compared to fentanyl, sufentanil was associated with shorter duration to extubation (Hazard ratio 1.31, 95% CI, 1.20-1.41) and ICU discharge (Hazard ratio 1.63, 95% CI, 1.38-1.92), and remifentanil was associated with shorter duration to extubation (Hazard ratio 1.60, 95% CI, 1.40-1.84) and ICU discharge (Hazard ratio 2.02, 95% CI, 1.43-2.84). No significant differences in time to extubation (Hazard ratio 1.14, 95% CI, 0.92-1.41) and ICU discharge (Hazard ratio 1.31, 95% CI ,0.81-2.14) were found between sufentanil and remifentanil. No differences were observed between any two of the agents regarding ventilator mortality or ICU mortality. The effects were similar in patients with versus without surgery. Conclusions: Sufentanil and remifentanil may be superior to fentanyl in shortening the time to extubation and ICU discharge. The effects on ventilator mortality and ICU mortality appeared similar across these agents, while further research is warranted.